The Effect of TRIZ (OTSM) Training on Preschoolers’ Creativity and Philosophy of Use in Beh- Bahan - Mehr-Afsha, Jahangir; Deh-Dar, Sareh (Advances in Social Sciences Research Journal, 2018)
This study aimed to analyze the effect of TRIZ training on preschoolers’ creativity and philosophy of use in Beh-Bahan, Iran. The correspondents of the study included sixty (60) boy and girl Preschoolers that were randomly selected from different kindergarten schools in Beh-Bahan, Iran. The research instrument included Ravens, progressive mattris test, Torrance’s picture creativity question air; Alhen’s reasoning skill question air and TRIZ (OTSM) training method of inventive problem solving. The preschoolers were assimilated with Raven’s progressive matris test. The selected sixty (60) correspondents were then divided in to two groups of control and experimental groups. Both control and experimental groups were pre- tested with respect to creativity and philosophy of use, and then the experimental groups were trained by TRIZ training method for eight (8) weeks. Both control and experimental groups were post tested. After the training period, the gathered data was further examined by t- test, and analyzed by SPSS statistical tools. The findings of the study showed that: The posttest mean score and t-test value of both preschoolers’ creativity and philosophy of use differed significantly from those of pre- test. This indicated that TRIZ (OTSM) training of inventive problem solving had significant effect on both preschoolers’ creativity and philosophy of use.